2023
DOI: 10.3390/vaccines11061068
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of SARS-CoV-2 IgG Antibody Response among South African Adults: A Prospective Cohort Study

Abstract: This study assesses the durability of severe acute respiratory coronavirus-2 (SARS-CoV-2) anti-nucleocapsid (anti-N) immunoglobulin G (IgG) after infection and examines its association with established risk factors among South African healthcare workers (HCWs). Blood samples were obtained from 390 HCWs with diagnosis of coronavirus disease 2019 (COVID-19) for assay of the SARS-CoV-2 anti-N IgG at two time points (Phase 1 and 2) between November 2020 and February 2021. Out of 390 HCWs with a COVID-19 diagnosis,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…This may be partly due to the statistical challenge of eliminating the interference of various vaccine formulations on inter-host differences. However, for COVID-19 vaccines, studies have already demonstrated the impact of host factors such as age[13], medical history[14], and genetic background[15, 16] on post-vaccination antibody levels. Nevertheless, these studies mainly report statistical aspects, with limited exploration of underlying mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…This may be partly due to the statistical challenge of eliminating the interference of various vaccine formulations on inter-host differences. However, for COVID-19 vaccines, studies have already demonstrated the impact of host factors such as age[13], medical history[14], and genetic background[15, 16] on post-vaccination antibody levels. Nevertheless, these studies mainly report statistical aspects, with limited exploration of underlying mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Since IgG antibodies against SC2 can persist for months, it is more likely that patient 2 had a gastrointestinal infection due to an infectious agent other than SC2, such as Campylobacter jejuni , mycoplasma pneumoniae, cytomegalovirus, Epstein–Barr virus, influenza, hepatitis E or Zika. 3 Were these pathogens excluded as causes of the gastrointestinal infection that preceded GBS in patient 2?…”
mentioning
confidence: 99%